2017
DOI: 10.1136/bmjopen-2017-016400
|View full text |Cite
|
Sign up to set email alerts
|

Decisional needs assessment of patients with complex care needs in primary care: a participatory systematic mixed studies review protocol

Abstract: IntroductionPatients with complex care needs (PCCNs) often suffer from combinations of multiple chronic conditions, mental health problems, drug interactions and social vulnerability, which can lead to healthcare services overuse, underuse or misuse. Typically, PCCNs face interactional issues and unmet decisional needs regarding possible options in a cascade of interrelated decisions involving different stakeholders (themselves, their families, their caregivers, their healthcare practitioners). Gaps in knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Prior to fsQCA, a variable is converted into set membership degree, including the three qualitative anchor points of complete subjection (CSP), intersection point (IP), and complete dissubjection point (CDP), to determine the orientation of the case after assignment [ 57 ]. Based on previous research, the upper and lower quartiles were selected as CSP and CDP, respectively, and the average values of the upper and lower quartiles were selected as IP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to fsQCA, a variable is converted into set membership degree, including the three qualitative anchor points of complete subjection (CSP), intersection point (IP), and complete dissubjection point (CDP), to determine the orientation of the case after assignment [ 57 ]. Based on previous research, the upper and lower quartiles were selected as CSP and CDP, respectively, and the average values of the upper and lower quartiles were selected as IP.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate solution is included in the operation of some meaningful logical remainder and is generally considered superior while the latter does not include any operation of logical remainder. Rihoux et al [ 57 ] noted that the first two solutions are mainly observed in QCA analysis cases and stipulated that when an antecedent condition occurs in both the parsimonious and the intermediate solutions, it is called the core condition. If an antecedent condition occurs only in the intermediate solution, it is called an auxiliary condition.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, internet-based resources and websites are increasingly used by patients with bipolar disorder to meet their information needs. In this regard, patients with mood disorder do not differ greatly from patients with other complex medical conditions in the primary care setting [27]. Searching the internet for information on medical conditions is a well-accepted approach [28].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was previously published (29). We conducted a systematic mixed studies review (qualitative, quantitative, and mixed methods studies) with an international multidisciplinary team including primary care researchers and knowledge users (patient-partner, practitioners, service managers and policy makers) (30,31).…”
Section: Methodsmentioning
confidence: 99%